2008
DOI: 10.1152/ajpregu.00677.2007
|View full text |Cite
|
Sign up to set email alerts
|

Passive leg movement enhances interstitial VEGF protein, endothelial cell proliferation, and eNOS mRNA content in human skeletal muscle

Abstract: The present study used passive limb movement as an experimental model to study the effect of increased blood flow and passive stretch, without enhanced metabolic demand, in young healthy male subjects. The model used was 90 min of passive movement of the leg leading to a 2.8-fold increase ( P < 0.05) in blood flow without a significant enhancement in oxygen uptake. Muscle interstitial fluid was sampled with microdialysis technique and analyzed for vascular endothelial growth factor (VEGF) protein and for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
92
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 39 publications
9
92
0
Order By: Relevance
“…Under both CON and BLK conditions, the increase in pulmonary V O 2 due to passive movement was only 0.04 l/min compared with 0.49 l/min when knee extension was actively performed at 15 W. Similarly, leg V O 2 increased by only 0.02 l/min during passive limb movement compared with 0.32 l/min from baseline to active exercise at 15 W. Therefore, the increases in pulmonary V O 2 and leg V O 2 were only 8 and 6%, respectively, of the total increase compared with active exercise. Previous work using a similar passive exercise protocol reported nearly identical and apparently unavoidable increases in both pulmonary and leg V O 2 (12,13). Thus, while passive movement appears to result in a minor increase in metabolism, the contribution of work performed by the subject was Ͻ6% of the actual V O 2 required to perform active knee extension at 15 W. The increase in pulmonary and leg V O 2 may be due to joint and limb stabilization during passive movement.…”
Section: O 2 Transport and Utilization During Passive Movementmentioning
confidence: 68%
“…Under both CON and BLK conditions, the increase in pulmonary V O 2 due to passive movement was only 0.04 l/min compared with 0.49 l/min when knee extension was actively performed at 15 W. Similarly, leg V O 2 increased by only 0.02 l/min during passive limb movement compared with 0.32 l/min from baseline to active exercise at 15 W. Therefore, the increases in pulmonary V O 2 and leg V O 2 were only 8 and 6%, respectively, of the total increase compared with active exercise. Previous work using a similar passive exercise protocol reported nearly identical and apparently unavoidable increases in both pulmonary and leg V O 2 (12,13). Thus, while passive movement appears to result in a minor increase in metabolism, the contribution of work performed by the subject was Ͻ6% of the actual V O 2 required to perform active knee extension at 15 W. The increase in pulmonary and leg V O 2 may be due to joint and limb stabilization during passive movement.…”
Section: O 2 Transport and Utilization During Passive Movementmentioning
confidence: 68%
“…However, discrepancies exist regarding the magnitude and duration of movement-induced hyperemia during passive exercise. Alterations in body position may be responsible for these discrepancies since we have reported a transient increase in LBF during supine passive movement (14,22,23), whereas others have reported that the elevated LBF was sustained for the duration of passive movement when performed in the upright seated position (15,16). This concept is supported by central and peripheral hemodynamic differences due to manipulation in body position as rest and during exercise (2,7,10,20,25).…”
mentioning
confidence: 71%
“…hemodynamics; blood flow; perfusion pressure PASSIVE MOVEMENT, unlike voluntary exercise, occurs without a marked increase in skeletal muscle metabolism (15,36). By the removal of the increase in metabolism associated with exercise, the independent effect of movement on central and peripheral hemodynamic mechanisms governing exercise hyperemia can be identified and studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After 30 min of rest in the supine position local anesthesia (1 ml of lidocaine, 20 mg/ml without epinephrine) was administered to the skin and subcutaneous tissue. Three microdialysis probes were inserted in the m. vastus lateralis of each leg in a direction parallel with the muscle fiber orientation (17). Membrane length, outer diameter, and molecular cut-off of the probes (custom made) were 40 mm, 0.22 mm, and 6,000 Da, respectively.…”
Section: Methodsmentioning
confidence: 99%